Bamboo-based hard carbon sodium battery negative electrode material and preparation method thereof
Through solvent thermal acid dissolution, discharge plasma sintering and chemical vapor deposition technologies, the problems of high impurity content, high production costs and difficult to adjust the pore structure of bamboo-based hard carbon materials are solved, and efficient and low-cost hard carbon materials are achieved, which significantly improves the electrochemical performance and cycle life of sodium ion batteries.
Patent Information
- Application Number
- CN202411672128.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Bamboo-based hard carbon has problems such as high impurity content, high production cost, and difficult pore structure adjustment, which limits its application in the field of sodium ion batteries.
Solvent thermal acid solution is used to carry out deep ash removal and decomposition, combined with discharge plasma sintering technology to achieve high efficiency and energy-saving carbonization, and carbon coating is carried out through chemical vapor deposition technology to reduce surface defects and specific surface area.
It significantly reduces the impurity content and production cost of hard carbon materials, improves the uniformity and electrochemical properties of materials, and extends the cycle life of sodium ion batteries.
Smart Images

Figure CN119560508A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to but is not limited to the technical field of electrode materials, and in particular relates to a bamboo-based hard carbon sodium negative electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are one of the most widely used energy storage systems. However, the scarcity of lithium resources, high costs, and poor safety have greatly limited the application of lithium-ion batteries in low-speed electric vehicles, large-scale energy storage, and other fields. In recent years, sodium-ion batteries have attracted more and more attention from scientific researchers due to their low cost, high safety, and good low-temperature performance. In the future, they are expected to replace lithium batteries in energy storage and other fields.
[0003] Although sodium ion batteries are promising, they still have problems such as high cost and low energy density. In particular, the cost and performance of negative electrode materials have severely limited the application of sodium ion batteries. Although hard carbon materials are considered to be ideal materials for sodium negative electrodes, the selection of raw materials and the processing technology of hard carbon still need to be explored. At present, the fastest-applied materials on the market are biomass-based hard carbon materials, including coconut shell carbon, straw carbon, wood carbon, starch carbon, etc., but there are also problems such as batch instability, high production cost, large specific surface area, and many impurities. Traditional methods of deashing and impurity removal generally use acid or alkali for cleaning, such as patent 201010246305.2, which mentions "add 80-300ml of acid or alkali for every 100g of dry plant raw materials and soak for 3-50h; the plant raw materials are pollen, rice husks, sugarcane stalks, walnut shells, bamboo, wine lees and sawdust". However, due to surface tension and other problems, it is difficult to completely remove metal impurities by soaking, which will affect the purity of the final carbon material. Moreover, most carbonization methods still use inert atmosphere electric furnace heating. Patent 202210603931.5 mentions that "the biomass is pretreated by mechanical ball milling, vibration milling or swelling, and then the pretreated biomass material is carbonized and cracked under an inert atmosphere to obtain high closed-pore biomass-derived hard carbon." Traditional heating methods have high energy consumption and are time-consuming. The hard carbon material obtained is prone to excessive accumulation of carbon layers, which affects the embedding and removal of sodium ions.
[0004] Bamboo has many varieties, grows fast, and is widely distributed throughout the country. It is cheap, environmentally friendly and renewable, and has a high carbon yield for preparing hard carbon. It is a high-quality biomass precursor material. However, bamboo-based hard carbon still has problems such as high impurity content, high production cost, and difficult to adjust pore structure.
[0005] In view of the above analysis, the technical problems that urgently need to be solved in the prior art are: bamboo-based hard carbon has high impurity content, high production cost, and difficult to adjust pore structure. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a method for preparing a bamboo-based hard carbon sodium negative electrode material, which utilizes solvent thermal acid decomposition to achieve the purpose of deep deashing and impurity removal, realizes efficient and energy-saving carbonization of bamboo-based materials through discharge plasma sintering technology, greatly shortens the production cycle, and inhibits excessive accumulation of carbon layers. Finally, chemical vapor deposition technology is used to perform carbon coating treatment to reduce surface defects and reduce the specific surface area of the hard carbon material, thereby preparing a new type of bamboo-based sodium ion battery negative electrode material and achieving excellent electrochemical performance.
[0007] The present invention is achieved by a method for preparing a bamboo-based hard carbon sodium negative electrode material, the specific steps of which are as follows:
[0008] S1, wash the natural bamboo, dry it in the sun, scrape off the surface green bamboo with a knife, and cut it into small pieces;
[0009] S2, preparing a dilute acid solution, vacuum immersing the bamboo in the dilute acid solution, and then transferring the bamboo into a hydrothermal kettle to perform a solvent thermal acidolysis reaction under high temperature and high pressure conditions to deash and remove impurities, while softening the bamboo;
[0010] S3, after solvent thermal acid hydrolysis, the bamboo material is washed, dried, and pre-carbonized using a tube furnace. After pre-carbonization, the sample is ball-milled, sieved, and then transferred to a graphite mold and placed in a spark plasma sintering furnace for high-temperature sintering and carbonization;
[0011] S4, subjecting the carbon powder treated with discharge plasma to ultrasonic vibration, re-screening, and then chemical vapor deposition carbon coating to obtain a bamboo-based hard carbon sodium negative electrode material.
[0012] Furthermore, the natural bamboo is selected from moso bamboo, moso bamboo, phoenix tail bamboo, water bamboo, purple bamboo, ci bamboo, single bamboo, square bamboo, arhat bamboo, arrow bamboo, thorny bamboo, nan bamboo, brown bamboo, Phyllostachys chinensis, four-season bamboo, etc. The ash content and impurity elements such as Al, Ba, Fe, and Na in the bamboo green are higher than those in the bamboo flesh. Scraping off the bamboo green and retaining the bamboo flesh can improve the uniformity and purity of the carbonized material.
[0013] Furthermore, the acid used for solvent thermal acidolysis is selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, oxalic acid, citric acid, acetic acid, and phosphoric acid, and the concentration of the dilute acid solution is 0.1-2 mol / L. The bamboo is vacuum impregnated in the dilute acid solution for 12-48 hours to ensure sufficient infiltration of the acid solution, and then transferred to a hydrothermal kettle for solvent thermal acidolysis reaction at a reaction temperature of 80-180° C. for a reaction time of 2-24 hours. The solvent thermal acidolysis reaction has two purposes: one is to fully remove impurity elements and ash such as Al, Fe, and Ca in the bamboo, and the other is to decompose part of the cellulose in the bamboo, soften the bamboo, and form a more loose and porous structure.
[0014] Further, the bamboo is then cleaned with distilled water, and vacuum-heated and dried at a heating temperature of 80-150° C. for a heating time of 12-48 hours.
[0015] Furthermore, the bamboo material after solvent thermal acidification is subjected to a low-temperature pre-carbonization reaction using a tubular furnace, with a pre-carbonization temperature of 400-800° C., a heating time of 2-10 h, and a heating rate of 2-10° C. / min.
[0016] Furthermore, after the pre-carbonization, the product is subjected to ball milling and screening treatment, with a ball milling speed of 200-800 rpm and a ball milling time of 0.5-10 h; and then subjected to a vibration screening machine treatment with a screen size of 200-500 meshes.
[0017] Furthermore, the ground carbon powder is transferred to a graphite mold and placed in a spark plasma sintering furnace for high-temperature carbonization sintering. The carbonization temperature is 1000-1600°C, the carbonization time is 1-20min, the heating rate is 200-1000°C / min, and the pressure applied by the upper and lower pressure heads is 20-100MPa. After the furnace body cools to room temperature, the sample is taken out and then crushed and vibrated and screened. Spark plasma sintering can achieve a fast and efficient high-temperature carbonization process to achieve the purpose of energy saving and consumption reduction. At the same time, the rapid temperature rise and fall and pulse current shock can avoid the accumulation of carbon structure, maintain a large interlayer spacing of carbon layers in the bamboo charcoal structure, and facilitate the embedding and removal of sodium ions.
[0018] Furthermore, the carbon coating is finally carried out through chemical vapor deposition reaction. The carbon source gas selected for chemical vapor deposition is one or more of methane, ethylene, benzene, propylene, butene, acetylene, CO, butane, and the protective gas is hydrogen, argon, nitrogen or a mixture thereof. The reaction temperature is 800-1200°C, the reaction time is 10-120min, and the final product has a uniformly coated carbon content of 1%-15%. Chemical vapor deposition carbon coating can reduce the edge defects of bamboo-based carbon materials, reduce the specific surface area of the materials, and improve the overall uniformity of the materials, which is conducive to improving the batch problem of biomass carbon materials and improving the first-cycle coulomb efficiency of hard carbon negative electrodes.
[0019] Another object of the present invention is to provide a bamboo-based hard carbon sodium negative electrode material prepared by the preparation method of the bamboo-based hard carbon sodium negative electrode material, wherein the hard carbon negative electrode material has an ash content of 0-0.5% and a specific surface area of 1-8 m 2 / g, carbon interlayer spacing d002 value is 0.36-0.40nm, hard carbon particle size is 2-30μm, compaction density is 1.2-2.0g / cm 3 .
[0020] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0021] First, the traditional way of deashing and removing impurities is through acid washing and alkali washing. However, since the biomass materials and derived carbon materials are hydrophobic structures and mostly porous structures, it is difficult to achieve full infiltration and complete removal of ash. The present invention adopts solvent thermal acid hydrolysis technology, which can greatly reduce the surface tension of water under high temperature and high pressure environment, so that it can fully infiltrate the bamboo material and achieve the purpose of deep deashing and impurity removal. At the same time, under the environment of high temperature acid, part of the cellulose will decompose to soften the bamboo material, which is conducive to forming a looser and more porous structure. The ash content of the hard carbon negative electrode material finally obtained is only 0-0.5%.
[0022] In the high-temperature carbonization process, the traditional electric furnace heating mode not only has high energy consumption and long reaction time, but also the slow heating and cooling process easily causes the recrystallization of carbon materials, resulting in the accumulation of aromatic structures, which is not conducive to the embedding of sodium ions. The present invention adopts a discharge plasma sintering method, and in the process of pressurization, the plasma generated by the pulse current is used to achieve rapid high-temperature carbonization sintering, and the heating rate can reach up to 1000℃ / min, which can greatly shorten the reaction time, reduce the sintering temperature, and improve production efficiency. At the same time, the rapid pulse current impact can maintain the microstructure of the material to the greatest extent, avoid the accumulation of carbon layers, and maintain a large interlayer spacing, which is conducive to the embedding and removal of sodium ions.
[0023] Traditional biomass hard carbon materials often have batch problems and uneven product quality, which is determined by the uncontrollable growth of the biomass material itself. After carbonization, the present invention uses chemical vapor deposition to perform carbon coating. Under the premise of not affecting the intrinsic properties, it can greatly reduce the edge defects of biomass carbon materials, improve the uniformity of hard carbon materials, and minimize the batch instability of bamboo-based carbon materials. At the same time, carbon coating can reduce the specific surface area of the material and improve the first-cycle Coulomb efficiency of the hard carbon negative electrode.
[0024] Second, as auxiliary evidence of the inventiveness of the claims of the present invention, it is also reflected in the following important aspects:
[0025] (1) The expected benefits and commercial value of the technical solution of the present invention after transformation are:
[0026] The bamboo-based hard carbon sodium negative electrode material and preparation method proposed in the present invention have the characteristics of low cost, low energy consumption and high capacity. The low-priced, environmentally friendly and renewable bamboo material is used as the raw material, combined with the low-energy consumption discharge plasma sintering method, the cost of the hard carbon material finally prepared can be reduced by 10-15% compared with the currently commercially available hard carbon, thereby reducing the cost of sodium ion batteries, making the cost of sodium ion batteries closer to that of lithium iron phosphate batteries, and thus realizing the replacement of lithium iron phosphate batteries in the fields of energy storage and so on.
[0027] (2) The technical solution of the present invention fills the technical gap in the industry at home and abroad:
[0028] The present invention proposes a solvent thermal acid hydrolysis method for the first time, which uses a high temperature and high pressure acidic environment to reduce the surface tension of water, thereby achieving full infiltration of bamboo materials, achieving the purpose of deep deashing and impurity removal, and greatly improving the uniformity and purity of hard carbon production, filling the technical gap in the industry at home and abroad. In addition, it is also the first time that the spark plasma sintering method is introduced into the preparation process of sodium negative electrode, providing a new strategy and idea for efficient and energy-saving hard carbon production, and this process has good scalability and can be used for high-temperature rapid carbonization of a variety of chemical raw materials, mineral raw materials and biomass raw materials.
[0029] Third, technical issues
[0030] In the prior art, the preparation of hard carbon sodium negative electrode materials usually relies on petrochemical-based raw materials or synthetic chemical materials, which are not only costly but also not environmentally friendly. In addition, it is difficult to achieve high controllability of the material structure during the preparation process of these materials, and the uniformity and purity of carbon materials are insufficient, resulting in limited electrochemical performance in sodium ion batteries, especially in terms of cycle stability, conductivity and volume expansion control. There is still much room for improvement.
[0031] Significant technological advancements:
[0032] 1. Environmental protection and sustainability
[0033] The present invention uses natural bamboo as raw material. Bamboo is a renewable resource with a short growth cycle and abundant resources, which significantly reduces the cost of raw materials and environmental impact. Compared with traditional petrochemical-based raw materials, this method has more environmental advantages and responds to the demand for sustainable development materials in the green energy field.
[0034] 2. Removal of impurities and homogenization
[0035] Through solvent thermal acidification and vacuum impregnation technology, the present invention effectively removes inorganic impurities and ash in bamboo materials and optimizes the purity of bamboo materials. This method not only improves the uniformity of the material, but also lays a good foundation for the subsequent carbonization process, thereby achieving higher carbonization efficiency and product quality.
[0036] 3. Unique pre-carbonization and sintering process
[0037] The spark plasma sintering technology was introduced. This method achieves the densification and graphitization of carbon materials through rapid high-temperature sintering, significantly enhancing the conductivity and structural stability of bamboo-based hard carbon materials. This technology has solved the problem of insufficient material density in the traditional pyrolysis carbonization process and improved the cycle stability of negative electrode materials.
[0038] 4. Innovative application of carbon coating technology
[0039] The surface of the carbon powder is coated by chemical vapor deposition (CVD) to form a uniform conductive carbon layer, which not only improves the conductivity of the material, but also effectively alleviates the volume expansion problem of the sodium negative electrode material during the charging and discharging process. This modification process significantly extends the cycle life of the sodium battery.
[0040] 5. Optimization design of process parameters
[0041] The present invention systematically optimizes the acid type, concentration, treatment time, reaction temperature and carbon coating conditions in the key process steps of solvent thermal acid hydrolysis, carbonization, sintering and surface treatment. The precise control of parameters ensures the high purity, high uniformity and excellent electrochemical performance of the final material.
[0042] 6. Significant improvement in electrochemical performance
[0043] By optimizing the microstructure and surface properties of bamboo-based hard carbon materials, the material exhibits excellent sodium ion embedding / de-embedding ability, significantly extended cycle life, and high capacity retention rate, which can meet the needs of the next generation of sodium ion batteries for high-performance negative electrode materials.
[0044] Industrial application potential:
[0045] 1. Low-cost large-scale production
[0046] The invention adopts natural bamboo as raw material, the raw material source is wide, the cost is low, and the preparation process is simple and easy, which is suitable for industrial large-scale production.
[0047] 2. Wide range of applications
[0048] The bamboo-based hard carbon sodium negative electrode material prepared by the present invention exhibits excellent performance in sodium ion batteries, is suitable for energy storage systems, electric vehicles and consumer electronics, and provides a new option for large-scale energy storage and low-cost battery technology.
[0049] 3. Meet national policy needs
[0050] This technology is in line with the current development trend of green energy and environmentally friendly materials, and is a strong support for the country's energy sustainable development strategy.
[0051] In summary, the present invention solves key problems in existing sodium battery negative electrode materials such as environmentally unfriendly resource utilization, high process complexity, and unstable material performance, significantly improves the electrochemical performance and production efficiency of the materials, and has important technical and industrial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a flow chart of a method for preparing a bamboo-based hard carbon sodium negative electrode material provided by an embodiment of the present invention;
[0053] Figure 2 is a scanning electron microscope image of a bamboo-based hard carbon material provided by an embodiment of the present invention;
[0054] Figure 3 is a cycle performance diagram of the bamboo-based hard carbon material provided by an embodiment of the present invention;
[0055] Figure 4 4 is a charge and discharge curve diagram of the bamboo-based hard carbon material provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0056] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0057] like Figure 1 As shown, the preparation method of the bamboo-based hard carbon sodium negative electrode material provided by the embodiment of the present invention comprises the following specific steps:
[0058] S1, wash the natural bamboo, dry it in the sun, scrape off the surface green bamboo with a knife, and cut it into small pieces;
[0059] S2, preparing a dilute acid solution, vacuum immersing the bamboo in the dilute acid solution, and then transferring the bamboo into a hydrothermal kettle to perform a solvent thermal acidolysis reaction under high temperature and high pressure conditions to deash and remove impurities, while softening the bamboo;
[0060] S3, after solvent thermal acid hydrolysis, the bamboo material is washed, dried, and pre-carbonized using a tube furnace. After pre-carbonization, the sample is ball-milled, sieved, and then transferred to a graphite mold and placed in a spark plasma sintering furnace for high-temperature sintering and carbonization;
[0061] S4, subjecting the carbon powder treated with discharge plasma to ultrasonic vibration, re-screening, and then chemical vapor deposition carbon coating to obtain a bamboo-based hard carbon sodium negative electrode material.
[0062] The preparation method of the bamboo-based hard carbon sodium negative electrode material provided by the present invention realizes the transformation of bamboo into high-performance sodium negative electrode material through a series of physical and chemical treatment steps. The specific working principle is as follows:
[0063] 1. Pretreatment of natural bamboo
[0064] First, the natural bamboo is preliminarily cleaned and cut. Bamboo contains a lot of inorganic impurities and surface green bamboo during its growth process, which affects the purity of the material and the subsequent carbonization effect. Therefore, after washing and drying the bamboo, use a knife to scrape off the surface green bamboo and cut it into small pieces for the subsequent solvent thermal treatment. This step ensures that the material is pure and has a high surface area, so that the subsequent deashing and softening treatments can be carried out more effectively.
[0065] 2. Solvent thermal acidification and deashing and impurity removal
[0066] The bamboo is immersed in a dilute acid solution and placed in a hydrothermal kettle, where a solvent thermal acidolysis reaction is carried out under high temperature and high pressure conditions to further remove inorganic impurities and ash from the bamboo. The acidolysis reaction not only removes minerals from the bamboo, but also effectively softens the bamboo fiber structure, which is beneficial for subsequent carbonization treatment. The high temperature and high pressure solvent thermal conditions help the acidolysis to proceed completely, ensuring the purity and uniformity of the internal structure of the bamboo, so that the final product has a higher carbon content and fewer impurities.
[0067] 3. Pre-carbonization and high temperature sintering carbonization
[0068] The acid-treated bamboo is pre-carbonized in a tube furnace to undergo a preliminary carbonization reaction at high temperature, thereby removing organic components and volatiles and forming a preliminary framework of bamboo-based carbon materials. Then, after being ball-milled, the material is placed in a graphite mold and subjected to high-temperature sintering and carbonization by spark plasma sintering. Spark plasma sintering provides a rapid high-temperature environment, which promotes the rapid carbonization and densification of carbon materials, thereby further enhancing the conductivity and structural stability of the material.
[0069] 4. Carbon coating and surface modification
[0070] The sintered carbon powder is ultrasonically vibrated and re-screened to ensure particle uniformity. Subsequently, chemical vapor deposition (CVD) carbon coating treatment is performed to form a uniform carbon coating layer on the surface of the material. This coating layer not only increases the conductivity of the material, but also effectively prevents the sodium electrode from volume expansion or electrolyte corrosion during the charge and discharge process, thereby improving the cycle stability and life of the electrode. The final product is a bamboo-based hard carbon sodium negative electrode material with high electrochemical performance, which is suitable for high-performance sodium-ion batteries.
[0071] The preparation method of the present invention can efficiently convert natural bamboo into battery materials, has the advantages of environmental protection and low cost, and shows good industrial application potential.
[0072] The natural bamboo is selected from moso bamboo, moso bamboo, phoenix tail bamboo, water bamboo, purple bamboo, ci bamboo, single bamboo, square bamboo, arhat bamboo, arrow bamboo, thorny bamboo, nan bamboo, brown bamboo, Phyllostachys chinensis, four-season bamboo, etc. The ash content and impurity elements such as Al, Ba, Fe, and Na in the green bamboo are higher than those in the bamboo flesh. Scraping off the green bamboo and retaining the bamboo flesh can improve the uniformity and purity of the carbonized material.
[0073] The acid used for solvent thermal acidolysis is selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, oxalic acid, citric acid, acetic acid, and phosphoric acid. The concentration of the dilute acid solution is 0.1-2 mol / L. The bamboo is vacuum impregnated in the dilute acid solution for 12-48 hours to ensure sufficient infiltration of the acid solution. The bamboo is then transferred to a hydrothermal kettle for solvent thermal acidolysis reaction at a reaction temperature of 80-180°C for a reaction time of 2-24 hours. The solvent thermal acidolysis reaction has two purposes: one is to fully remove impurity elements such as Al, Fe, Ca, and ash in the bamboo; the other is to decompose part of the cellulose in the bamboo, soften the bamboo, and form a looser and more porous structure.
[0074] The bamboo is then cleaned with distilled water and dried by vacuum heating at a temperature of 80-150°C for 12-48 hours.
[0075] The bamboo material after solvent thermal acid hydrolysis is subjected to low-temperature pre-carbonization reaction using a tubular furnace, with a pre-carbonization temperature of 400-800°C, a heating time of 2-10h, and a heating rate of 2-10°C / min.
[0076] After pre-carbonization, the product is subjected to ball milling and screening treatment, with a ball milling speed of 200-800 rpm and a ball milling time of 0.5-10 h; and then subjected to a vibration screening machine treatment with a screen mesh of 200-500 meshes.
[0077] The ground carbon powder is transferred to a graphite mold and placed in a spark plasma sintering furnace for high-temperature carbonization sintering. The carbonization temperature is 1000-1600℃, the carbonization time is 1-20min, the heating rate is 200-1000℃ / min, and the pressure applied by the upper and lower pressure heads is 20-100MPa. After the furnace body cools to room temperature, the sample is taken out and crushed and vibrated and screened. Spark plasma sintering can achieve a fast and efficient high-temperature carbonization process to achieve the purpose of energy saving and consumption reduction. At the same time, the rapid temperature rise and fall and pulse current shock can avoid the accumulation of carbon structure, maintain a large interlayer spacing of carbon layers in the bamboo charcoal structure, and facilitate the embedding and removal of sodium ions.
[0078] Finally, carbon coating is carried out through chemical vapor deposition reaction. The carbon source gas selected for chemical vapor deposition is one or more of methane, ethylene, benzene, propylene, butene, acetylene, CO, butane, and the protective gas is hydrogen, argon, nitrogen or their mixed gas. The reaction temperature is 800-1200℃, the reaction time is 10-120min, and the final product has a uniformly coated carbon content of 1%-15%. Chemical vapor deposition carbon coating can reduce the edge defects of bamboo-based carbon materials, reduce the specific surface area of the materials, and improve the overall uniformity of the materials, which is conducive to improving the batch problem of biomass carbon materials and improving the first-cycle coulomb efficiency of hard carbon negative electrodes.
[0079] Another object of the present invention is to provide a bamboo-based hard carbon sodium negative electrode material prepared by the preparation method of the bamboo-based hard carbon sodium negative electrode material, wherein the hard carbon negative electrode material has an ash content of 0-0.5% and a specific surface area of 1-8 m 2 / g, carbon interlayer spacing d002 value is 0.36-0.40nm, hard carbon particle size is 2-30μm, compaction density is 1.2-2.0g / cm 3 .
[0080] Embodiment 1:
[0081] Select bamboo as raw material, wash the bamboo, dry it in the sun, scrape off the surface bamboo green with a scraper, and cut it into small pieces of about 10 cm. Prepare 0.5mol / L dilute sulfuric acid solution, vacuum impregnate the bamboo for 24 hours, and then transfer it to a hydrothermal kettle, seal it and heat it at 100℃ for 10 hours, cool it and wash it with distilled water until it is neutral, put it in an oven, and dry it at 120℃ for 20 hours. Use a tubular furnace for pre-carbonization reaction, heat it at 500℃ for 5 hours under a nitrogen atmosphere, and the heating rate is 5℃ / min, then ball milling is carried out, and 300 mesh screen is used for screening. Then put the carbon powder into a graphite mold, use a discharge plasma sintering furnace for high temperature treatment, heat it to 1400℃ at 500℃ / min, and heat it for 10 minutes. Finally, cool it naturally and take out the sample, then crush and vibrate and screen it, and sieve it with a 300 mesh screen. Finally, the carbon coating reaction was carried out. The sample was placed in the center of a chemical vapor deposition furnace, heated to 1000°C with argon as the protective gas, and methane was introduced as the carbon source gas. The reaction lasted for 30 minutes to obtain a bamboo-based hard carbon negative electrode material. The hard carbon negative electrode material has an ash content of 0.3% and a specific surface area of 2.5 m 2 / g, the carbon layer spacing d002 value is 0.378nm, and the morphology is Figure 2 As shown, the half-cell was assembled for electrochemical performance testing, and the discharge cycle diagram was shown in Figure 3 , Figure 4 As shown, the bamboo-based hard carbon negative electrode material has a high specific capacity of 386 mAh / g and good cycle stability, and the platform capacity is above 210 mAh / g.
[0082] Embodiment 2:
[0083] Select arrow bamboo as raw material, wash the bamboo with clean water, dry it in the sun, scrape off the surface bamboo green, and cut it into small pieces of about 10 cm. Prepare 1mol / L dilute hydrochloric acid solution, vacuum impregnate the bamboo for 20 hours, then transfer it to a hydrothermal kettle, seal it and heat it at 90℃ for 15 hours, cool it and wash it with distilled water until it is neutral, put it in an oven, and dry it at 120℃ for 20 hours. Use a tubular furnace for pre-carbonization reaction, heat it at 550℃ for 5 hours under a nitrogen atmosphere, and the heating rate is 5℃ / min, then ball milling is performed, and 400 mesh screen is used for screening. Then put the carbon powder into the graphite mold, use a discharge plasma sintering furnace for high temperature treatment, heat it to 1300℃ at 800℃ / min, and heat it for 10 minutes. Finally, cool it naturally and take out the sample, then crush and vibrate it, and sieve it with a 400 mesh screen. Finally, a carbon coating reaction was carried out. The sample was placed in the center of a chemical vapor deposition furnace, heated to 1000°C with an argon-hydrogen mixture as the protective gas, and methane was introduced as the carbon source gas. The reaction was carried out for 30 minutes to obtain a bamboo-based hard carbon negative electrode material.
[0084] The preparation of bamboo-based hard carbon proposed in the present invention is applied in the field of sodium ion batteries and used as a negative electrode material for sodium ion batteries. It can then be widely used in the fields of low-temperature energy storage, low-speed electric vehicles, household energy storage power supplies, etc. to replace lithium iron phosphate batteries.
[0085] The ash content of the hard carbon negative electrode material of the present invention can reach less than 0.5%, with high purity. A sodium ion battery half-cell was assembled based on bamboo-based hard carbon, and the electrochemical performance was tested. The charge and discharge cycle diagram is shown in FIG. Figure 3 , Figure 4 As shown, the bamboo-based hard carbon negative electrode material has a high specific capacity of 386 mAh / g in the first cycle, which is a significant improvement compared to the specific capacity of 300-330 mAh / g of commercially available hard carbon materials. This is mainly attributed to the richer pore structure of the bamboo-based material and the appropriate carbon layer spacing formed by the discharge plasma sintering technology, which is more conducive to the embedding and extraction of sodium ions. In addition, the discharge platform area capacity reaches more than 210 mAh / g, which comes from the adsorption of sodium ions by a large number of closed-pore structures formed by rapid sintering. The bamboo-based hard carbon material also has good cycle stability. Combined with the low-cost and low-energy production process, it has broad application prospects in actual production and manufacturing.
[0086] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a bamboo-based hard carbon sodium negative electrode material, characterized in that: The specific steps are as follows: S1, wash the natural bamboo, dry it in the sun, scrape off the surface green bamboo with a knife, and cut it into small pieces; S2, preparing a dilute acid solution, vacuum immersing the bamboo in the dilute acid solution, and then transferring the bamboo into a hydrothermal kettle to perform a solvent thermal acidolysis reaction under high temperature and high pressure conditions to deash and remove impurities, while softening the bamboo; S3, the bamboo material after solvent thermal acid hydrolysis is washed, dried, and pre-carbonized using a tube furnace; After pre-carbonization, the sample is ball-milled, sieved, and then transferred into a graphite mold and placed in a spark plasma sintering furnace for high-temperature sintering and carbonization. S4, subjecting the carbon powder treated with discharge plasma to ultrasonic vibration, re-screening, and then chemical vapor deposition carbon coating to obtain a bamboo-based hard carbon sodium negative electrode material.
2. The method for preparing the bamboo-based hard carbon sodium negative electrode material according to claim 1, characterized in that: The natural bamboo is selected from moso bamboo, moso bamboo, phoenix tail bamboo, water bamboo, purple bamboo, ci bamboo, single bamboo, square bamboo, arhat bamboo, arrow bamboo, thorny bamboo, nan bamboo, brown bamboo, Phyllostachys pubescens, and four-season bamboo; the ash content and the content of impurity elements such as Al, Ba, Fe, and Na in the bamboo green are higher than those in the bamboo flesh. Scraping off the bamboo green and retaining the bamboo flesh can improve the uniformity and purity of the carbonized material.
3. The method for preparing the bamboo-based hard carbon sodium negative electrode material according to claim 1, characterized in that: The acid used in the solvent thermal acidolysis is selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, oxalic acid, citric acid, acetic acid and phosphoric acid, the concentration of the dilute acid solution is 0.1-2 mol / L, the bamboo is vacuum impregnated in the dilute acid solution for 12-48 hours to ensure sufficient infiltration of the acid solution, and then the bamboo is transferred to a hydrothermal kettle for solvent thermal acidolysis reaction at a reaction temperature of 80-180°C for a reaction time of 2-24 hours. The solvent thermal acidolysis reaction has two purposes: one is to fully remove Al, Fe, Ca impurity elements and ash in the bamboo, and the other is to decompose part of the cellulose in the bamboo, soften the bamboo, and form a looser and more porous structure.
4. The method for preparing the bamboo-based hard carbon sodium negative electrode material according to claim 1, characterized in that: The bamboo is then cleaned with distilled water and dried by vacuum heating at a temperature of 80-150°C for 12-48 hours.
5. The method for preparing the bamboo-based hard carbon sodium negative electrode material according to claim 1, characterized in that: The bamboo material after solvent thermal acid hydrolysis is subjected to low-temperature pre-carbonization reaction using a tubular furnace, with a pre-carbonization temperature of 400-800°C, a heating time of 2-10h, and a heating rate of 2-10°C / min.
6. The method for preparing the bamboo-based hard carbon sodium negative electrode material according to claim 1, characterized in that: After pre-carbonization, the product is subjected to ball milling and screening treatment, with a ball milling speed of 200-800 rpm and a ball milling time of 0.5-10 h; and then subjected to a vibration screening machine treatment with a screen mesh of 200-500 meshes.
7. The method for preparing the bamboo-based hard carbon sodium negative electrode material according to claim 1, characterized in that: The ground carbon powder is transferred to a graphite mold, placed in a spark plasma sintering furnace, and subjected to high-temperature carbonization sintering. The carbonization temperature is 1000-1600°C, the carbonization time is 1-20min, the heating rate is 200-1000°C / min, and the pressure applied by the upper and lower pressure heads is 20-100MPa. After the furnace body is cooled to room temperature, the sample is taken out and then crushed and vibrated and screened. Spark plasma sintering can realize a fast and efficient high-temperature carbonization process to achieve the purpose of energy saving and consumption reduction. At the same time, rapid temperature rise and fall and pulse current shock can avoid the accumulation of carbon structure, maintain a large interlayer spacing of carbon layers in the bamboo charcoal structure, and facilitate the embedding and removal of sodium ions.
8. The method for preparing the bamboo-based hard carbon sodium negative electrode material according to claim 1, characterized in that: Finally, carbon coating is carried out through chemical vapor deposition reaction. The carbon source gas selected for chemical vapor deposition is one or more of methane, ethylene, benzene, propylene, butene, acetylene, CO, butane, and the protective gas is hydrogen, argon, nitrogen or their mixture. The reaction temperature is 800-1200°C, the reaction time is 10-120min, and the final product has a uniformly coated carbon content of 1%-15%. Chemical vapor deposition carbon coating can reduce the edge defects of bamboo-based carbon materials, reduce the specific surface area of the material, and improve the overall uniformity of the material, which is beneficial to improve the batch problem of biomass carbon materials and improve the first-cycle coulomb efficiency of the hard carbon negative electrode.
9. A bamboo-based hard carbon sodium negative electrode material prepared by the method for preparing a bamboo-based hard carbon sodium negative electrode material according to any one of claims 1 to 8, characterized in that: The hard carbon negative electrode material has an ash content of 0-0.5% and a specific surface area of 1-8m 2 / g, carbon interlayer spacing d002 value is 0.36-0.40nm, hard carbon particle size is 2-30μm, compaction density is 1.2-2.0g / cm 3 .
Citation Information
Patent Citations
Hard carbon material for power and energy-storage battery and preparation method thereof
CN101916845A
Biomass-based hard carbon, preparation method thereof and application of biomass-based hard carbon in sodium-ion battery
CN115020643A
Method for preparing hard carbon material through spark plasma flash firing and application
CN113120877A
Method for rapidly carbonizing bagasse
CN116495718A
Performance regulation and control method of bamboo powder hard carbon negative electrode material for sodium ion battery
CN118744980A
Cited By
Preparation method of biomass sodium ion battery hard carbon negative electrode material and product
CN121823534A
Method for synergistically producing hard carbon and green methanol by moso bamboo carrying biomass solid waste
CN122010088A